An approach to synergistic and dynamic service evolution in clouds. (2015) - Wang, Zhe; Cheng, Guojian
The proposed research will focus on developing a novel approach on software service evolution in computing clouds. The approach will support dynamic evolution of the software service in clouds via a set of discovered evolution patterns. An initial survey informed us that such an approach does not exist yet and is in urgent need. Serviceoriented computing is a computing paradigm that exploits both web services and serviceoriented architecture (SOA) as fundamental elements for developing software systems. This paradigm changes the way software system are designed, architected, delivered and consumed. The serviceoriented paradigm is emerging as a new way to engineer system that are composed of and exposed as services for use through standardised protocols. Cloud computing is rapidly emerging as the new computing paradigm of the coming decade. The idea of virtualisation not just hardware but software resources as well has attracted the attention of academicians as well as the industry. Cloud computing offers a viable solution to the problem of addressing scalability and availability for largescale application and of sharing resources.